A Study on Empty Fruit Bunch Powder and Oil Palm Frond Powder as Green Corrosion Inhibitor for Oil and Gas Application - TAMALMANI, KAUSALYA (2021)
Corrosion has been a major setback for most industries, notably oil and gas industries. This is because most of the metallic equipment utilized in the industry is in constant interaction with crude oils, gas, petroleum products, atmosphere, water, and soil. The midstream region involving the pipeline and other transport methods that are utilized to transport crude and refined petroleum from the production segment up to refineries are continuously in contact with the impurities contained in the crude and refined petroleum, which makes the corrosion issue unavoidable. Due to this, the utilization of corrosion inhibitors in the oil and gas industry to minimize the corrosion issue is being practiced to date. Most of the inhibitors utilized are conventional corrosion inhibitors, which provoked the toxicity concern among the industries because it can cause significant effects on ecosystems. Hence, the biomass wastes have gained attention from the researchers to be used as green corrosion inhibitors, as an alternative for conventional corrosion inhibitors since biomass wastes are being produced on a larger scale and often go unused.